Effects of Antioxidant Therapy on Leukocyte Myeloperoxidase and Cu/Zn-Superoxide Dismutase and Plasma Malondialdehyde Levels in Experimental Colitis - Ergul Belge Kurutas; Ali Cetinkaya; Ertan Bulbuloglu; Bulent Kantarceken (Hindawi Limited, 2005)
The aim of the present study was to evaluate the effects of N-acetylcysteine (NAC) and L-carnitine (LCAR) supplementations on polymorphonuclear leukocytes myeloperoxidase (MPO) and Cu/Zn-superoxide dismutase (Cu/Zn-SOD) and plasma malondialdehyde (MDA) in acetic acid (AA)-induced ulcerative colitis model. The mean polymorphonuclear leukocyte MPO and Cu/Zn-SOD activity was significantly higher in the colitis group than in the control group. Both NAC and LCAR pretreatment markedly decreased MPO and Cu/Zn-SOD activity compared to colitis group. AA administration significantly increased the levels of plasma MDA in comparison with controls. However, NAC and LCAR administration to the AA-treated rats significantly reduced the MDA levels compared to colitis group. In conclusion NAC and LCAR could be beneficial agents in restoring the circulating proinflammatory mediators.